The Low Conductivity of Geobacter uraniireducens Pili Suggests a Diversity of Extracellular Electron Transfer Mechanisms in the Genus Geobacter - Tan, Yang; Adhikari, Ramesh Y.; Malvankar, Nikhil S.; Ward, Joy E.; Nevin, Kelly P.; Woodard, Trevor L.; Smith, Jessica A.; Snoeyenbos-West, Oona L.; Franks, Ashley E.; Tuominen, Mark T.; Lovley, Derek R. (Frontiers in Microbiology, 2016)
Studies on the mechanisms for extracellular electron transfer in Geobacter species have primarily focused on Geobacter sulfurreducens, but the poor conservation of genes for some electron transfer components within the Geobacter genus suggests that there may be a diversity of extracellular electron transport strategies among Geobacter species. Examination of the gene sequences for PilA, the Type IV pilus monomer, in Geobacter species revealed that the PilA sequence of Geobacter uraniireducens was much longer than that of G. sulfurreducens. This is of interest because it has been proposed that the relatively short PilA sequence of G. sulfurreducens is an important feature conferring conductivity to G. sulfurreducens pili. In order to investigate the properties of the G. uraniireducens pili in more detail, a strain of G. sulfurreducens that expressed pili comprised of the PilA of G. uraniireducens was constructed. This strain, designated strain GUP, produced abundant pili, but generated low current densities and reduced Fe(III) very poorly. At pH 7 the conductivity of the G. uraniireducens pili was 3 x 10-4 S/cm, much lower than the previously reported 5 x 10-2 S/cm conductivity of G. sulfurreducens pili at the same pH. Consideration of the likely voltage difference across pili during Fe(III) oxide reduction suggested that G. sulfurreducens pili can readily accommodate maximum reported rates of respiration, but that G. uraniireducens pili are not sufficiently conductive to be an effective mediator of long-range electron transfer. In contrast to G. sulfurreducens and G. metallireducens, which require direct contact with Fe(III) oxides in order to reduce them, G. uranirreducens reduced Fe(III) oxides occluded within microporous beads, demonstrating that G. uraniireducens produces a soluble electron shuttle to facilitate Fe(III) oxide reduction. The results demonstrate that Geobacter species may differ substantially in their mechanisms for long-range electron transport and that it is important to have information beyond a phylogenetic affiliation in order to make conclusions about the mechanisms by which Geobacter species are transferring electrons to extracellular electron acceptors.